2023
DOI: 10.1002/mrm.29798
|View full text |Cite
|
Sign up to set email alerts
|

A 128‐channel receive array for cortical brain imaging at 7 T

Abstract: PurposeA 128‐channel receive‐only array for brain imaging at 7 T was simulated, designed, constructed, and tested within a high‐performance head gradient designed for high‐resolution functional imaging.MethodsThe coil used a tight‐fitting helmet geometry populated with 128 loop elements and preamplifiers to fit into a 39 cm diameter space inside a built‐in gradient. The signal‐to‐noise ratio (SNR) and parallel imaging performance (1/g) were measured in vivo and simulated using electromagnetic modeling. The his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…A previous modeling study by Vaidya et al 17 showed that ≳32 receive loops would capture most of the central uiSNR at field strengths 3, 7, and 9.4 T, and by extrapolation of data presented in Figure 2 of this article, also at 10.5 T. However, this prediction is based on simulations of idealized conditions using a sphere and a spherical shell substrate that was completely tiled by idealized loop receivers with evenly distributed currents on the loop. Although there is experimental data (including in this article) confirming this prediction at 3 T and 7 T 46,65 no previous experimental data exists at fields greater than 7 T. Therefore, the specific conclusions of the Vaidya et al 17 article need to be modified to state that in realistic head receive arrays composed of loops, 32 and even 64 elements are insufficient to capture central uiSNR at field >10 T, whereas they do capture it at 7 T (and likely at lower magnetic fields). This conclusion was experimentally confirmed for the 63-channel array (Figure 9) and is also aligned with another numerical simulation study 31 where it was demonstrated that the central SNR performance of a 64-channel loop receiver drops to 80% at 11 T, whereas it is nearly 100% at 7 T (see figure 3 in Lattanzi and Sodickson).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A previous modeling study by Vaidya et al 17 showed that ≳32 receive loops would capture most of the central uiSNR at field strengths 3, 7, and 9.4 T, and by extrapolation of data presented in Figure 2 of this article, also at 10.5 T. However, this prediction is based on simulations of idealized conditions using a sphere and a spherical shell substrate that was completely tiled by idealized loop receivers with evenly distributed currents on the loop. Although there is experimental data (including in this article) confirming this prediction at 3 T and 7 T 46,65 no previous experimental data exists at fields greater than 7 T. Therefore, the specific conclusions of the Vaidya et al 17 article need to be modified to state that in realistic head receive arrays composed of loops, 32 and even 64 elements are insufficient to capture central uiSNR at field >10 T, whereas they do capture it at 7 T (and likely at lower magnetic fields). This conclusion was experimentally confirmed for the 63-channel array (Figure 9) and is also aligned with another numerical simulation study 31 where it was demonstrated that the central SNR performance of a 64-channel loop receiver drops to 80% at 11 T, whereas it is nearly 100% at 7 T (see figure 3 in Lattanzi and Sodickson).…”
Section: Discussionsupporting
confidence: 56%
“…6,63,64 Moreover, the 63-channel array showed superior acceleration performance as compared to the 31-channel array, at both 7 T and 10.5 T, again consistent with previous work demonstrating that higher number of channels lead to higher acceleration at a given field strength. 46,65,66 EM simulations demonstrated that 31-and 63-loop elements in these arrays could capture most of the uiSNR centrally at 7 T. However, this is not the case at 10.5 T, where both the 31-and the 63-channel arrays fall far short of capturing the central uiSNR. A previous modeling study by Vaidya et al 17 showed that ≳32 receive loops would capture most of the central uiSNR at field strengths 3, 7, and 9.4 T, and by extrapolation of data presented in Figure 2 of this article, also at 10.5 T. However, this prediction is based on simulations of idealized conditions using a sphere and a spherical shell substrate that was completely tiled by idealized loop receivers with evenly distributed currents on the loop.…”
Section: Discussionmentioning
confidence: 96%
“…BC2 was another geometry with a larger diameter, which was associated with similar SAR than BC1 but more homogeneous B 1 + . 32,33 Detailed information on those coils' performance is provided in Figure S14.…”
Section: Discussionmentioning
confidence: 99%
“…The loops of the cylindrical 16-channel arrays were broken by four capacitors for tuning and matching (similarly, adjacent channels were decoupled using capacitors). In addition to the cylindrical pTx arrays, we also simulated two 16-rung birdcage coils, a high-pass birdcage coil (BC1) with dimensions matching the former of the cylindrical pTx arrays (coil diameter = 264 mm, length = 240 mm), and a band-pass shielded birdcage coil (BC2) 32,33 with a bigger coil diameter of 336 mm, coil length of 240 mm, shield diameter of 390 mm, and shield length of 360 mm. For BC1, we explored four distinct feedport configurations in the circularly polarized mode: (1) front-feeding, with ports positioned near the subject's forehead; (2) right-feeding, with ports situated on the right side of the subject's head; (3) back-feeding, with ports located toward the back of the subject's head; and (4) left-feeding, with ports in proximity to the left side of the subject's head.…”
Section: Ptx Arrays and Body Modelmentioning
confidence: 99%
“…Capturing this maximum achievable SNR requires the development of complex radiofrequency (RF) coils. Such developments have largely taken place for 7T and lower magnetic fields, leading to complex arrays with multichannel transmit and receive capabilities for imaging of the human head (e.g., (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)). This, however, is uncharted territory for the new frontier of ≳10T imaging.…”
Section: Introductionmentioning
confidence: 99%